Cold case flashbacks - Johnson, Janice (Janice Kay) (Johnson, Janice (Janice Kay). Unsolved mystery book., 2021)
"Twenty-five years after witnessing the murder of her mother, Gabriella Ortiz returns home to face the past she's repressed since childhood. Detective Jack Cowan is obsessed with solving the cold case and catching the killer who shattered her family--and his. As Gabby's buried memories start to surface, can Jack shield her from a faceless killer who is intent on destroying the future they're hoping to build?"--